Inguinal Hysterocele Mimics Mammary Tumour in Small Breed Dogs - Gupta, Nikita; Sangwan, Vandana; Kumar, Ashwani; Anand, Arun; Mahajan, Shashikant (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The study aims to highlight inguinal hysterocele as a common finding in small breed dogs presented with inguinal swelling mimicking  mammary tumor. Nine intact female dogs with a history of non-traumatic, left sided inguinal swelling were included in the study. The  dogs belonged to the breeds; Dachshund (n=3), Pug (n=2), Pomeranian (n=2) and Non-descript (n=2). Majority of these belonged to  middle age group and none had any recent history of parturition relating to swelling. On physical examination, the swelling was hard  and firm to touch and non-reducible. The chest radiograph corresponding to inguinal mammary tumor was negative for metastasis in all  the dogs. On ultrasonography of inguinal swellings, 3 out of 9 cases (33.33%) were confirmed for inguinal hernia as the small intestines  (n=2) or urinary bladder (n=1) were visualized in the swelling. The rest could not be confirmed as the herniated uterine horn and/or  omentum did not show any motility. All the dogs were operated under inhalant general anesthesia and a confirmed inguinal hysterocele  with either uterine horn or part of it as hernial content with or without other abdominal organs was discovered. Ovariohysterectomy  was done in all the cases along with the hernia repair from the same incision site leading to a successful outcome. In conclusion, inguinal  swelling in small breed female dogs must be evaluated for hysterocele before proceeding for surgery as it often mimics mammary tumour.
Keywords: Dogs; Hysterocele; Inguinal hernia; Mammary tumour; Ultrasonography